Building a low-carbon future in Shah Alam : Governance strategies and community engagement for sustainable development - Yusfida Ayu, Abdullah; Nor Baizura, Jamaluddin; Khalid, Zanudin; Marlyana Azyyati, Marzukhi; Ishak, Che Abdullah (Universiti Kebangsaan Malaysia, 2025)
A recognized way to accelerate the transition to a sustainable future is through the combination of sustainable development, which includes the Low Carbon City (LCC) practice, Local Authorities Empowerment, and Community Participation. Somehow, the issue of disorganized institutional management and administration may also result from these approaches. This dilemma was highlighted in the Malaysia LCC Masterplan, which indicated the need for institutional reform. Furthermore, local authorities must promote community awareness and encourage involvement in LCC efforts. The objective of this article is to examine the delivery of LCC for sustainable development through city governance and the community’s awareness in supporting the effort. The method applied scoping and document reviews, Expert Interviews, and a Focus Group Discussion (FGD). The participants for the Expert Interviews and FGD were selected using the Purposive Sampling method since the investigation required inputs from key players and communities related to LCC practice. The findings confirmed that city governance is vital in implementing LCC through many applications, like the institutional framework, practices, and delivery. Meanwhile, the outcome from the FGD demonstrated that community awareness and participation in LCC initiatives are relatively low due to a lack of communication approach and collaboration between stakeholders. LCC initiatives through a better governance approach. The outcome of this study is expected to transmit the direction of practicing Low Carbon City concept through city governance by considering public participation into the process.